2020
DOI: 10.1177/1938965520919106
|View full text |Cite
|
Sign up to set email alerts
|

Examining Risk-Reduction Behavior Toward Water Quality Among Restaurant Guests

Abstract: Globally, there is a growing concern about health threats from water pollution and its effects upon products used in the restaurant food preparation process. Thus, the use of contaminated water for commercial food preparation represents a high source of risk for disease-causing illnesses upon human health in both developed and developing countries. Using the Protection Motivation Theory, a convenience sampling of n = 506 Chinese residents and visitors, defined as non-Chinese residents born and sociali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 48 publications
(76 reference statements)
3
16
0
2
Order By: Relevance
“…Many academic reviews conclude that perceived threat is a core component and the most useful in understanding the practice of a variety of preventive health behaviours. According to the HBM, perceived threat refers to beliefs about the seriousness of a particular disease and how susceptibility they are to it (Berg & Lin, 2020;Bish & Michie, 2010;Carpenter, 2010;Cho et al, 2020;Janz & Becker, 1984;Manika & Golden, 2011;Weitkunat et al, 2003).…”
Section: Perceived Threatmentioning
confidence: 99%
“…Many academic reviews conclude that perceived threat is a core component and the most useful in understanding the practice of a variety of preventive health behaviours. According to the HBM, perceived threat refers to beliefs about the seriousness of a particular disease and how susceptibility they are to it (Berg & Lin, 2020;Bish & Michie, 2010;Carpenter, 2010;Cho et al, 2020;Janz & Becker, 1984;Manika & Golden, 2011;Weitkunat et al, 2003).…”
Section: Perceived Threatmentioning
confidence: 99%
“…Cho et al [34] studied restaurant customers' water quality concerns caused by water pollution, and indicated that water quality significantly affects threat appraisal composed of severity and vulnerability. Chang and Lee [35] studied the risk of COVID-19 and health consciousness and confirmed that the risk of COVID-19 positively influences threat appraisal composed of severity and vulnerability.…”
Section: Relationships Among the Constructs 231 Relationship Between ...mentioning
confidence: 99%
“…According to Cho et al [34], water quality positively affects consumers' coping appraisal comprising self-efficacy and response efficacy. Chang and Lee's [35] study showed that people's health consciousness positively influences coping appraisal composed of self-efficacy and response efficacy.…”
Section: Relationship Between Awareness Of Food Waste Problem and Cop...mentioning
confidence: 99%
See 2 more Smart Citations